Accidental symmetries and massless quarks in the economical 3-3-1 model - Montero, J. C. [UNESP]; Sánchez-Vega, B. L. (American Physical Society (APS), 2015)
In the framework of a 3-3-1 model with a minimal scalar sector, known as the economical 3-3-1 model, we study its capabilities of generating realistic quark masses. After a detailed study of the symmetries of the model, before and after the spontaneous symmetry breaking, we find a remaining axial symmetry that prevents some quarks from gaining mass at all orders in perturbation theory. Since this accidental symmetry is anomalous, we also consider briefly the possibility of generating their masses for nonperturbative effects. However, we find that nonperturbative effects are not enough to generate the measured masses for the three massless quarks. Hence, these results imply that the economical 3-3-1 model is not a realistic description of the electroweak interaction.